Las trabajadoras del hogar en el Perú: Contexto actual, evolución normativa y posibles cambios - Kajatt Flores, Carlos (2019)
The way domestic house workers are treated is a direct inheritance of slavery and serfdom. Besides, house labour is usually associated with the female gender, whose labour is often undervalued and discredited. In this article, the author exposes the problem of housemaids and domestic workers in Peru. It goes through its definition, historical evolution, regulatory framework and a new bill in this regard. Likewise, it develops a legal and sociological analysis of the way in which housework legislations has evolved, allowing to visualize the advances and challenges that Peruvian society will have to face in order to suppress the inequality and discrimination the currently occurs in this kind of jobs.